IMPLEMENTASI PEMBINAAN PRAMUKA DALAM MEMBENTUK KARAKTER PERCAYA DIRI SISWA DI SD IES AL-GHUROBA KABUPATEN SORONG TAHUN AJARAN 2020/2021 - Afroh Nailil Hikmah; Arin Fitria Rizky (MISOOL: Jurnal Pendidikan Dasar, 2021)
Schools are institutions that are responsible for helping to develop knowledge as well as in the personality aspect. However, to achieve these educational goals, it can not only rely on school programs, one of the extracurricular programs implemented in schools is scouting as a place to develop the character that exists in students. This study aims to determine the efforts made by the scout coaches, the form of activities, and also the supporting and inhibiting factors for the formation of students' self-confidence. The type of research used in this research is qualitative research. By conducting direct observations and interviews between researchers and school principals as ambiguous, scout coaches, and also students involved in the implementation of scouting. This study shows that the efforts made by scout coaches, namely: planning student training schedules, implementing scouting activities are carried out by giving assignments, evaluating scouting activities, and giving sanctions to students who violate the rules. The forms of activities carried out by scout coaches in forming a confident character are Routine training, Camping, Level Contest, Exploration, or Hiking. The factors that influence the formation of students' self-confidence in SD IES Al_Ghuroba are the planned implementation of learning that has been arranged, experienced coaches, adequate learning media, based on the vision and mission of Pondok Tahfidz Al-Ghuroba.